Impacto da educação continuada realizada pelo laboratório de monitoramento externo da qualidade na acuidade dos resultados dos exames citopatológicos do colo do útero - Ázara, Cinara Zago Silveira (2014)
The effectiveness of cytopathology exams demands high quality training, continued education and highly skilled professionals to guarantee a reliable, accurate exam, aimed at reducing false results. Objective: To evaluate the effect of a continued education program conducted by the External Quality Control Monitoring Laboratory (LabMEQ), assessing the agreement of the results and internal quality control indicators. Methods: To analyze the agreement of the results, 19,826 exams conducted between 2007 and 2011 and selected through the cervical cancer data system (SISCOLO) were evaluated, 9,798 of these exams having been performed prior to the implementation of continued education and 10,028 after implementation. The statistical analysis was performed using the chi-square test, with p-values < 0.05 being considered statistically significant and the kappa coefficient was calculated. To analyze the internal quality control indicators, 185,194 exams performed between 2007 and 2012 were evaluated. Data for these exams were obtained from the SISCOLO, with 98,133 having been performed prior to the implementation of continued education and 87,061 after implementation. The following indicators were calculated: positivity index (PI), percentage of exams compatible with a high-grade squamous intraepithelial lesion (HSIL/satisfactory), percentage of atypical squamous cells among all abnormal smears (ASC/abnormal) and the ratio between atypical squamous cells and intraepithelial lesions (ASC/SIL). Continued education was provided every two months to the professionals from the participating laboratories in the form of theoretical and practical classes to discuss discordant cases and the standardization of cytomorphological criteria. Results: After the implementation of continued education, a reduction was found in the percentage of false-negative results that lead to delays in clinical management in eight laboratories and there was an improvement in the rate of false-positive results in five. There was no improvement observed in the unsatisfactory results. The agreement of the cytopathology exam results, according to the clinical management, remained excellent in three laboratories (kappa > 0.80), increased from good (kappa > 0.60 and < 0.80) to excellent (kappa > 0.80) in seven and from excellent to good in two laboratories. The agreement in the identification of the metaplastic epithelium, which was poor (kappa = 0.25), was classified as excellent after implementation of the continued education program (kappa = 0.95). The agreement of the results, according to the diagnosis, improved significantly following continued education in unsatisfactory cases (p<0.001), in cases of atypical squamous cells of undetermined significance (ASC-US) and atypical squamous cells cannot exclude HSIL (p<0.001), low-grade squamous intraepithelial lesions (p<0.001) and atypical glandular cells (p<0.001). Following implementation of the continued education program, the positivity index (PI) remained within recommended limits in four laboratories. In another four laboratories, the PI progressed from below the limits to within the recommended standards. In one laboratory, the PI remained low, in two laboratories, it remained very low, and in one, it increased from very low to low. The HSIL/satisfactory remained within the recommended limits in five laboratories, while in three laboratories it progressed from below the recommended levels to >0.4% of the total number of satisfactory exams, and in four laboratories it remained below the standard limit. Both the percentage of ASC/abnormal and the ratio ASC/SIL remained within recommended levels in all the laboratories investigated. Conclusion: The results of this study show that the continued education program conducted by LabMEQ with the laboratories was effective as a measure aimed at standardizing cytomorphological criteria, since there was an improvement in the reproducibility of the results and in the indicators of internal quality control, leading to a reduction in the number of false results.